An enhanced Nonenzymatic Electrochemical Glucose Sensor Based on Copper‐Palladium Nanoparticles Modified Glassy Carbon Electrodes. Issue 8 (18th April 2018) - Li, Zhan‐Hong; Zhao, Xue‐Ling; Jiang, Xin‐Cheng; Wu, Yi‐Hua; Chen, Cheng; Zhu, Zhi‐Gang; Marty, Jean‐Louis; Chen, Qing‐Song
Abstract: Novel copper‐palladium nanoparticles modified glassy carbon electrodes (Cu−Pd/GC) with enhanced nonenzymatic sensing for glucose were facilely prepared by one‐step electrodeposition. The structure and composition of the prepared nanoparticles were characterized by XRD, SEM, TEM and EDS, respectively. The electrode modified process was characterized by electrochemical impedance spectroscopy. Cyclic voltammetry and chronoamperometric experiments were used to evaluate the electrocatalytic activities of the electrodes toward glucose. The surface morphology and the electrocatalytic activities of Cu−Pd/GC was compared to Pd and Cu nanoparticles modified glassy carbon electrodes (Pd/GC and Cu/GC), respectively. Thanks to homogeneous distribution of Cu−Pd nanoparticles and the synergistic effect of Cu and Pd atoms, Cu−Pd/GC exhibited the highest sensitivity (298 μA mM −1  cm −2 ) and the widest linear amperometric response (0.01 mM to 9.6 mM, R 2 =0.996) toward glucose compared to Pd/GC and Cu/GC. The detection limit of Cu−Pd/GC was 0.32 μM (S/N=3). In addition, the as‐prepared Cu−Pd/GC glucose sensor also exhibited exceptional capabilities of anti‐interference, reproducibility and long‐term stability. The as‐prepared sensor was also evaluated for determination of glucose concentration in human blood serum samples, which exhibited high reliability and accuracy, having great potential in clinical application. Abstract :